2017
DOI: 10.1038/ni0217-246a
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Corrigendum: WNK1 kinase balances T cell adhesion versus migration in vivo

Abstract: In the version of this article initially published, the citation of Figure 3 in the second paragraph of the third subsection (Chromatin: the nexus of phenotype and the environment) is incorrect. That should cite Figure 2, as follows: "From an evolutionary perspective, two extreme models of how such complexity might be generated and regulated can be envisaged 95 (Fig. 2). " The error has been corrected in the HTML and PDF versions of the article.Erratum: Sall1 is a transcriptional regulator defining microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Each bar graph represents the means ± SEM phosphorylation of RA-GEF is necessary for chemokine-dependent Rap1 activation. On the other hand, WNK1-deficient T cells demonstrated an augmented chemokine-dependent Rap1 activation [37], suggesting that phosphorylation by WNK1 inhibits Rap1 activation. In this study, we demonstrated that WNK1 phosphorylated RA-GEF, and basal dephosphorylation of RA-GEF was critical for chemokinedependent Rap1 activation in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Each bar graph represents the means ± SEM phosphorylation of RA-GEF is necessary for chemokine-dependent Rap1 activation. On the other hand, WNK1-deficient T cells demonstrated an augmented chemokine-dependent Rap1 activation [37], suggesting that phosphorylation by WNK1 inhibits Rap1 activation. In this study, we demonstrated that WNK1 phosphorylated RA-GEF, and basal dephosphorylation of RA-GEF was critical for chemokinedependent Rap1 activation in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%